Increased expression of CD40 ligand on systemic lupus erythematosus lymphocytes. - Koshy, M (J Clin Invest, 1996)
The specificity of T cell help for B cell activation and differentiation is maintained by the brief expression on the T cell surface, following T cell receptor-mediated triggering, of CD40 ligand (CD40L). Interaction of T helper (Th) cell CD40L with B cell CD40 induces B cell activation, cell surface expression of activation antigens, proliferation, and initiation of immunoglobulin isotype switch. We predicted that in patients with systemic lupus erythematosus (SLE), in whom Th cell-dependent production of autoantibodies results in immune complex-mediated tissue damage, CD40L expression might be augmented, prolonged, or abnormally regulated. Baseline expression of CD40L was increased in some SLE patients studied, when compared with control subjects. While Th cells from normal subjects (n = 14) and rheumatic disease control patients (n = 9) showed maximal expression of CD40L, after in vitro activation with phorbol myristate acetate (PMA) and ionomycin, at 6 h of culture with diminished levels observed at 24 and 48 h, Th cells from SLE patients (n = 19) maintained high level cell surface expression of CD40L through 24 and 48 h of culture. The prolonged expression of CD40L was functionally significant, as 24 h-activated SLE T cells, when cocultured with target B cells, induced greater B cell surface CD80 (B7-1) expression than did 24 h-activated normal T cells. These results document impaired regulation of CD40L expression in SLE T cells and identify an important potential target for therapy in this systemic autoimmune disease.